A prebiotic-based biopolymeric encapsulation system for improved survival of Lactobacillus rhamnosus. (October 2020) - Azam, Muhammad; Saeed, Muhammad; Pasha, Imran; Shahid, Muhammad
Abstract: Fructooligosaccharides (FOS) improve viability of probiotics and gastrointestinal health. FOS and alginate as encapsulation material, can provide better structure of beads to improve the survival of probiotics. The present study focused on FOS extraction from banana peel to encapsulate L. rhamnosus and explore its in vitro survival through structural interactive optimization of encapsulation materials. FOS and sodium alginate (SA) were used for encapsulation of L. rhamnosus with different formulations, e.g., Mo (100% SA), M1 (75% SA + 25% FOS), M2 (50% SA + 50% FOS), M3 (25% SA + 75% FOS) and M4 (FOS 100%). The stability of free and encapsulated L. rhamnosus was assessed using gastrointestinal conditions. All the treatments provided better encapsulation efficiency except M4. Microencapsulation significantly maintained viability of L. rhamnosus using simulated gastric conditions, bile salt, low pH and during storage. M2 was considered as the best encapsulation treatment for survival of L. rhamnosus . The SA beads have pores but addition of FOS improved the structure of the beads. Fourier transform infrared spectrometry results showed the presence of FOS and SA in the respective treatments. Principal component analysis (PCA) explained differences among bead formulations using spectral data. In simulated gastric juice, maximum viability was observed (8.5 ± 0.1 log CFU/mL) due to increased concentration of FOS. The FOS were extracted from banana peel and successfully used as a prebiotic encapsulation material for effective delivery of L. rhamnosus . The different combinations of wall materials provided an opportunity to develop beads with better structure and protection. Graphical abstract: Image 1